The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/1467-9477.00029
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Policy as Battlefield: A Study of National Interest and Party Motives

Abstract: In no other policy arena are party unity and national unity considered as critical as in security and foreign policy. Party unity on foreign policy is viewed as a national security strategy of particular importance in times of international crisis and uncertainty, or as an expression of party strategy and ideological considerations. Through an empirical study of programs, congresses, voters and ideology of the Swedish parties 1945^1993, we show that the presence or absence of tension in the international syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
0
7
0
6
Order By: Relevance
“…More recently, however, research on foreign policy has suggested that foreign and security policy is indeed an important area of disagreement among political parties (see, e.g., Bjereld and Demker, 2000;Özkeçeci-Taner, 2005;Schuster and Maier, 2006;Devine, 2009;Kaarbo, 2012;Calossi et al, 2013;Clare, 2014;Verbeek and Zaslove, 2015;Pijovic, 2016;Chryssogelos, 2018;Hofmann, 2017). Because foreign policy, including military missions, can be salient to voters and influence voting behaviour (cf.…”
Section: Party-political Contestation Of Military Missionsmentioning
confidence: 99%
“…More recently, however, research on foreign policy has suggested that foreign and security policy is indeed an important area of disagreement among political parties (see, e.g., Bjereld and Demker, 2000;Özkeçeci-Taner, 2005;Schuster and Maier, 2006;Devine, 2009;Kaarbo, 2012;Calossi et al, 2013;Clare, 2014;Verbeek and Zaslove, 2015;Pijovic, 2016;Chryssogelos, 2018;Hofmann, 2017). Because foreign policy, including military missions, can be salient to voters and influence voting behaviour (cf.…”
Section: Party-political Contestation Of Military Missionsmentioning
confidence: 99%
“…Em contrapartida, a elevada quantidade de matérias de política externa aprovadas no governo Lugo indica o isolamento das questões internacionais da disputa política doméstica. A natureza distinta da política externa, com poucas matérias de cunho redistributivo, a elevada centralização decisória nas mãos da presidência (Insaurralde 2014), o baixo incentivo eleitoral para os membros do Legislativo (Canes-Wrone, Howell & Lewis 2008) e o efeito do compromisso internacional assinado pelo presidente ex-ante (Bjereld & Demker 2000) são elementos que contribuem para a delegação da condução dos assuntos exteriores do Legislativo ao Executivo.…”
Section: Iv2 Instituições E Política Externaunclassified
“…The first, labelled 'bipartisanship' and the 'two presidencies' thesis, argues that the political dispute between domestic groups 'stops at the water's edge ' (McCormick and Wittkopf 1990). It holds that the anarchy generated by the international system produces incentives for political parties to adopt unified positions on the foreign policies pursued by executives, in contrast with their behaviour towards domestic politics (Bjereld and Demker 2000). Thus domestic politics are characterised by high levels of party polarisation and political disputes, and international politics by low levels of party polarisation as well as political consensus (King 1986).…”
Section: Legislative Support For Presidential Domestic and Foreign Pomentioning
confidence: 99%